A phylogeny and evolutionary natural history of mesoamerican toads (Anura: Bufonidae: Incilius) based on morphology, life history, and molecular data - Mendelson Iii, Joseph R.; Mulcahy, Daniel G.; Williams, Tyler S.; Sites Jr., Jack W. (Zootaxa, 2011)
We combine mitochondrial and nuclear DNA sequence data with non-molecular (morphological and natural history) data to conduct phylogenetic analyses and generate an evolutionary hypothesis for the relationships among nearly every species of Mesoamerican bufonid in the genus Incilius. We collected a total of 5,898 aligned base-pairs (bp) of sequence data from mitochondrial (mtDNA: 12S–16S, cyt b, ND2–CO1, including tRNAsTRP–TYR and the origin of light strand replication; total 4,317 bp) and nuclear (CXCR4 and RAG1; total 1,581 bp) loci from 52 individual toads representing 37 species. For the non-molecular data, we collected 44 characters from 29 species. We also include Crepidophryne, a genus that has not previously been included in molecular analyses. We present results of parsimony and Bayesian analyses for these data separately and combined. Relationships based on the non-molecular data were poorly supported and did not resolve a monophyletic Incilius (Rhinella marina was nested within). Our molecular data provide significant support to most of the relationships. Our combined analyses demonstrate that inclusion of a considerably smaller dataset (44 vs. 5,898 characters) of non-molecular characters can provide significant support where the molecular relationships were lacking support. Our combined results indicate that Crepidophryne is nested within Incilius; therefore, we place the former in the synonymy of the latter taxon. Our study provides the most comprehensive evolutionary framework for Mesoamerican bufonids (Incilius), which we use as a starting point to invoke discussion on the evolution of their unique natural history traits.